THE NEW PARADIGM OF SURAH AL FATIHAH BASED ON THE KEY CONCEPTS OF SOCIAL INTERPRETATION OF DAWAM RAHARJO - Janah, Miftahul; Haerudin, Haerudin (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2021)
When interpreting the Qur'an, a mufassir needs a paradigm and a foundation as the procedures and stages that become his reference. This paper attempts to discuss the paradigm and concept of interpretation promoted by Dawam Rahardjo, namely al-Fātiḥah as the Qur'an in a nutshell which is contained in the work of the Ensiklopedi Al-Quran: Tafsir Sosial Berdasarkan Konsep-Konsep Kunci. Two objectives in this study, first, the arguments that make al-Fātiḥah a paradigm and the extent to which these arguments can be justified. Second, steps, systematics and forms of interpretation by positioning al-Fātiḥah as a paradigm and its shortcomings in interpreting the Qur'an. This research is in the form of library research in the form of descriptive-analysis and uses content analysis as the analytical method used. This discussion concludes that there are two verses of the Qur'an, namely QS. Ali Imran (03): 07 and QS. al-Hijr (15): 87 as the basis and form three conceptual frameworks of al-Fātiḥah as a paradigm of interpretation of the Qur'an, namely the term ummu al-kitab as the attribution of surah al-Fātiḥah, the two ummu al-kitab referred to as muḥkām and the last term al-sab'u al-maṡāni which is also understood as al-Fātiḥah. The weakness in the argument that is built is in the redefinition of muḥkām or mutasyabīh which do not have clear standards and references. While the form of interpretation with this concept ends with a systematic form of thematic presentation with two steps or procedures, namely departing from the key terms in Surat al-Fātiḥah (inductive) and starting from other than Surat al-Fātiḥah then returning to Surat al-Fātiḥah (deductive). The first procedure has difficulties in developing the -evolutionist dimension-, while the second procedure will be very subjective because of the difficulty of matching the interpreted verse with the terms in Surah al-Fātiḥah.